EXTENDING STUDENTS’ MASTERY OF VOCABULARY LEARNED THROUGH PICTIONARY GAME - Marcy S Ferdinandus; Fatimatuz Zahra Rahayaan (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2020)
This study is aimed to help the students learn new vocabularies, meanings, and their function in sentences through Pictionary game at the first grade of SMP Negeri 14 Ambon. It also directly extended the new vocabularies learned into practice writing simple sentences. It is a Classroom Action Research design which stands under the mix method, quantitative- qualitative. The data was collected through test and classroom observation and it is directed to answer the three research questions; 1) how Pictionary Game helps the students in learning vocabularies, the meanings and functions of words, 2) how students apply the vocabularies learned into simple sentences in the extended Pictionary game activities, 3) how is the students’ attitude changes during the teaching and learning process. The result of the study exposed that students successfully acquired the vocabularies through the game. The extended activities of pictionary game helped the students to practice writing simple sentences using the vocabularies learned. It also exhibited that the students’ attitude change both during the game and the learning process.